The neural correlates of unsuccessful memory performance in MCI - Natalya eChechko (Frontiers in Aging Neuroscience, 2014)
People with MCI (mild cognitive impairment) are at an increased risk of developing Alzheimer's disease or other forms of dementia. Although the neural correlates of successful memory performance in MCI have been widely investigated, the neural mechanisms involved in unsuccessful memory performance remain unknown. The current study examines the differences between patients with stable amnestic MCI with multiple deficit syndromes and healthy elderly controls in relation to the neural correlates of both successful and unsuccessful encoding and recognition. 46 subjects (27 controls, 19 MCI) from the HelMA (Helmholtz Alliance for Mental Health in an Ageing Society) completed a comprehensive neuropsychological test battery and participated in an fMRI experiment for associative face-name memory. In patients, the areas of frontal, parietal and temporal cortices were less involved during unsuccessful encoding and recognition. A temporary dysfunction of the top-down control of frontal or parietal (or both) areas might result in a non-selective propagation of task-related information to memory.